Applying systems‐based thinking to build better IEP relationships: a case for relational coordination. Issue 3 (19th July 2020) - Singh, Shailen; Keese, Jeffrey
Abstract : This paper explores methods by which the Individualized Education Plan (IEP) development process can be improved through the use of systems‐based thinking, specifically through the use of Gittell's (2016) Relational Coordination Model. IEP development meetings have been described as meaningless rituals where parents often leave feeling ostracized from their child's academic experience due to an overemphasis on academic jargon and procedure (Rock, 2000; Salas, 2004). Systems‐based thinking would encourage administrators to empower parents as equal partners in the IEP development process, as originally intended by the Individuals with Disabilities Education Act of 1994. Furthermore, using Relational Coordination as a framework for work‐group structure would also allow school officials to create meaningful relationships with parents based on trust, thus resulting in a more positive IEP development experience and more robust educational plans.